2017
DOI: 10.15252/embj.201694914
|View full text |Cite
|
Sign up to set email alerts
|

Mfn2 is critical for brown adipose tissue thermogenic function

Abstract: Mitochondrial fusion and fission events, collectively known as mitochondrial dynamics, act as quality control mechanisms to ensure mitochondrial function and fine‐tune cellular bioenergetics. Defective mitofusin 2 (Mfn2) expression and enhanced mitochondrial fission in skeletal muscle are hallmarks of insulin‐resistant states. Interestingly, Mfn2 is highly expressed in brown adipose tissue (BAT), yet its role remains unexplored. Using adipose‐specific Mfn2 knockout (Mfn2‐adKO) mice, we demonstrate that Mfn2, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
221
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(236 citation statements)
references
References 57 publications
13
221
2
Order By: Relevance
“…In keeping with these data, BAT‐specific Mfn2 deletion through Ucp1 ‐Cre causes BAT lipohypertrophy and cold intolerance . The effects linked to Mfn2 ablation in adipose depots are not detected upon ablation of Mfn1 . These findings thus support the notion that the alterations detected in BAT are not dependent on mitochondrial fusion, but on a different function of MFN1 and MFN2.…”
Section: Contacts Between Mitochondria and Other Organellessupporting
confidence: 82%
See 2 more Smart Citations
“…In keeping with these data, BAT‐specific Mfn2 deletion through Ucp1 ‐Cre causes BAT lipohypertrophy and cold intolerance . The effects linked to Mfn2 ablation in adipose depots are not detected upon ablation of Mfn1 . These findings thus support the notion that the alterations detected in BAT are not dependent on mitochondrial fusion, but on a different function of MFN1 and MFN2.…”
Section: Contacts Between Mitochondria and Other Organellessupporting
confidence: 82%
“…These observations suggest that the mechanisms linked to Mfn2 deficiency are not a consequence of alterations in mitochondrial fusion but are rather linked to its tethering function. Mfn2 ablation in adipose tissues obtained by crossing Mfn2 loxP/loxP mice with mice expressing the Cre recombinase under the adiponectin promoter leads to enhanced body weight and fat mass, which was linked to a reduction in energy expenditure and in BAT thermogenesis [3]. In keeping with these data, BAT-specific Mfn2 deletion through Ucp1-Cre causes BAT lipohypertrophy and cold intolerance [169].…”
Section: Metabolic Impact Of Alterations In Proteins Participating Inmentioning
confidence: 71%
See 1 more Smart Citation
“…Indeed, deficient mouse embryonic fibroblasts (MEFs) in either Mfn1 or Mfn2 present highly fragmented mitochondria compared to the tubular and interconnected mitochondrial network observed in wild-type (WT) cells [3]. Beside its role in MT fusion, MFN 2 is also implicated in the formation of Endoplasmic Reticulum (ER)-MT contact sites [6] and in MT-lipid droplets interaction [7].The mechanism by which mitofusins mediate MT fusion is not fully understood, although it was suggested that MFN 1 and MFN 2 form homo-or hetero-oligomeric complexes by interacting in trans between neighbouring mitochondria, thereby promoting their tethering and subsequent fusion of MOM [8].OPA1, whose gene mutation is associated with a dominant optic atrophy disease [9] (Table 1), is localized to the MIM and the MT intermembrane space. Opa1 −/− cells present fragmented mitochondrial morphology, although some MOM fusion events were described [10].…”
mentioning
confidence: 99%
“…Indeed, deficient mouse embryonic fibroblasts (MEFs) in either Mfn1 or Mfn2 present highly fragmented mitochondria compared to the tubular and interconnected mitochondrial network observed in wild-type (WT) cells [3]. Beside its role in MT fusion, MFN 2 is also implicated in the formation of Endoplasmic Reticulum (ER)-MT contact sites [6] and in MT-lipid droplets interaction [7].…”
mentioning
confidence: 99%